A novel approach to generate and extract audio watermark. (1st January 2014) - Wang, Chundong; Bo, Guangming
This paper proposes a combination of audio watermarking algorithm based on the wavelet transform and the Fourier transform. After the binary watermark image preprocessing, wavelet transform is taken for the audio, then the discrete Fourier transform is taken for the wavelet transform approximation component coefficients. Finally, the amplitude of the Fourier transform coefficients is quantised to embed the watermark. In the watermark extraction process, the original audio signal is not required. This paper describes the detailed process. Lastly, the simulation tests confirm the robustness and transparency.